The use of early, mild hypothermia in the treatment of stable, spontaneous, supra tentorial, intracerebral haemorrhage - Andrean, Rusin (2009)
Haemorrhagic stroke or spontaneous intracerebral haemorrhage is a devastating condition that usually carries a poor prognosis and the treatment options has been very limited. The use of therapeutic hypothermia in ischaemic stroke has been published with some encouraging results but not definite. The objective of the study is to see the effect of mild hypothermia in the early post haemorrhagic stroke patient with a stable condition assessed using standard stroke outcome score in seven days, 30 days and 90 days. A prospective non randomised study was done with the sample of confirmed haemorrhagic stroke patients presenting to Hospital Universiti Sains Malaysia, Kubang Kerian, Kelantan between the ages of 18 to 80 years. Patients with haemorrhagic stroke that was confirmed on CT scan, and did not undergo any surgical intervention (including ventriculostomy) were offered to be recruited into the study. The patients who consented underwent therapeutic hypothermia using an intravascular cooling catheter for 24 hours and then a period of slow rewarming, all these in an intensive care setting. Patients who did not consent to the procedure were treated as per standard haemorrhagic stroke treatment protocol and taken as control. All patients would then be assessed in seven days, 30 days and 90 days using the National Institute of Health Stroke Scale (NIHSS) and Modified Rankin Scale. A total of 24 patients were recruited. In the interventional ann, six patients were recruited. Two of the patients however died in the first week of the therapy. In the control ann, 18 patients were recruited and 3 died before the 90 days follow up. There was a statistically significant improvement of the mRS score of the hypothermia group compared to the control group at 30 days and 90 days follow up. Using the NIHSS score, the seven days, 30 days and 90 days follow up showed a little improvement in the hypothermia group compared to the control group, but statistically significant. It can be concluded that the use of mild hypothermia is feasible and may be adjunctive to other treatment in the management of haemorrhagic stroke. However, due to the study limitation, we recommend a larger, multicentred trial to be done on early mild hypothermia on haemorrhagic stroke.